Tree and Stand Aerial Volume Tables for Sal - Tiwari, K. P.; Parthasarthy, V. (Indian Forester, 1979)
Tree and Stand Aerial Volume Tables for Sal (Shorea robusta) were prepared on 1:10,000 Panchromatic aerial photographs of Timli Block in Doon Valley. It was found that Photo height 2 Ã— Crown diameter explained 51.95% of variation in tree volume with a standart error of estimate of 58.6%. Similarly the combi-nation of variables Photo height + Crown closure, Average crown diameter explained 49% of variation in Stand volume with a standard error of estimate of 25.72%. the usefulness of aerial volume tables in the context of forest inventory have been highlighted.